2016
DOI: 10.3906/vet-1506-29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxytocin on milk proteins and fatty acid profile inSahiwal cows during lactation periods

Abstract: Bovine milk, a rich source of proteins and fatty acids, has a beneficial impact on physicochemical and organoleptic properties. The current study was planned to identify oxytocin's effects on protein and fatty acid profiles of cow milk (the Sahiwal breed) at various lactation stages (early, middle, and late) under a controlled atmosphere and feeding inputs. Examination of milk protein and fatty acid profiles by urea polyacrylamide gel electrophoresis and gas chromatography-mass spectrometry respectively reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…It has been shown in Sahiwal dairy cows that oxytocin has considerable effects on some milk minerals like Na, Cl and Cu, respectively, were higher (19.74, 9.39 and 146.89%), while K and lactose decreased by 10.06 and 0.39%, respectively (Hameed et al 2016), while, Akhtar et al (2012) showed that milk production improved by oxytocin injection in Buffalo.…”
Section: ____________________________________________________________mentioning
confidence: 98%
“…It has been shown in Sahiwal dairy cows that oxytocin has considerable effects on some milk minerals like Na, Cl and Cu, respectively, were higher (19.74, 9.39 and 146.89%), while K and lactose decreased by 10.06 and 0.39%, respectively (Hameed et al 2016), while, Akhtar et al (2012) showed that milk production improved by oxytocin injection in Buffalo.…”
Section: ____________________________________________________________mentioning
confidence: 98%
“…Milk fat is the most complex of all the natural fats as it contains many different fatty acids. The fatty acids profile of milk is associated with many factors such as animal origin (breed and selection), stage of lactation, mastitis, ruminal fermentation, feed-related factors, seasonal and regional effects [5][6][7][8]. Almost 98% of the fats in bovine milk are made up of triacylglycerides [9] and the remaining approximate 2% is made up of diacylglycerides, cholesterol, phospholipids, and free fatty acids [10].…”
Section: Introductionmentioning
confidence: 99%